Human mitochondrial ribosomes can switch their structural RNA composition - Rorbach, Joanna (Proc Natl Acad Sci U S A, 2016)
The recent developments in cryo-EM have revolutionized our access to previously refractory structures. In particular, such studies of mammalian mitoribosomes have confirmed the absence of any 5S rRNA species and revealed the unexpected presence of a mitochondrially encoded tRNA (mt-tRNA) that usurps this position. Although the cryo-EM structures resolved the conundrum of whether mammalian mitoribosomes contain a 5S rRNA, they introduced a new dilemma: Why do human and porcine mitoribosomes integrate contrasting mt-tRNAs? Human mitoribosomes have been shown to integrate mt-tRNA(Val) compared with the porcine use of mt-tRNA(Phe). We have explored this observation further. Our studies examine whether a range of mt-tRNAs are used by different mammals, or whether the mt-tRNA selection is strictly limited to only these two species of the 22 tRNAs encoded by the mitochondrial genome (mtDNA); whether there is tissue-specific variation within a single organism; and what happens to the human mitoribosome when levels of the mt-tRNA(Val) are depleted. Our data demonstrate that only mt-tRNA(Val) or mt-tRNA(Phe) are found in the mitoribosomes of five different mammals, each mammal favors the same mt-tRNA in all tissue types, and strikingly, when steady-state levels of mt-tRNA(Val) are reduced, human mitoribosome biogenesis displays an adaptive response by switching to the incorporation of mt-tRNA(Phe) to generate translationally competent machinery.